THE STORY "LIFE ON THE MISSISSIPPI " BY MARK TWAIN (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
"Life on the Mississippi" by Mark Twain is a seminal work that intertwines autobiography, history, and storytelling to depict life along the Mississippi River during the 19th century. This article examines the book’s themes, narrative techniques, and historical significance, focusing on its portrayal of the river's influence on American culture and identity. Through an interdisciplinary lens, it explores the text’s literary, historical, and sociocultural value, shedding light on Twain’s perspective as both a humorist and social commentator.